Stages of Development of Children’s Choir Art in Uzbekistan on the Example of Shermat Yormatov - qizi, Farangis Ikromova Yigitali (European Journal of Life Safety and Stability (2660-9630), 2022)
this article talks about the development of children’s choir art in Uzbekistan and the role of composer Shermat Yormatov in this cross-section of art. In addition, opinions about children’s art are explained in detail in the article.